2004
DOI: 10.1095/biolreprod.104.030387
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Regions of the Mouse Cyclin A1 Gene, Ccna1, Confer Male Germ-Cell Specific Expression and Enhancer Function1

Abstract: The gene encoding mouse cyclin A1, Ccna1, is expressed at highest levels in late pachytene-diplotene spermatocytes, where it is required for meiotic cell division. To begin to understand the mechanisms responsible for its highly restricted pattern of expression, transgenic mouse lines carrying constructs consisting of the cyclin A1 regulatory region fused with the reporter gene lacZ were generated. Analysis of tissue-specific and testicular cell-type-specific transgene expression indicated that sequences withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…These studies have demonstrated that short proximal promoter regions of meiotic genes are sufficient to specify their silencing in somatic cells and activation in germ cells [8][9][10][11][12][13]. A more detailed analysis of these minimal promoter regions revealed DNA regulatory elements harboring transcription factor binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated that short proximal promoter regions of meiotic genes are sufficient to specify their silencing in somatic cells and activation in germ cells [8][9][10][11][12][13]. A more detailed analysis of these minimal promoter regions revealed DNA regulatory elements harboring transcription factor binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…The essential role of Ccna1 in male germ cell development and the concurrent expression of cyclin A1 mRNA and protein suggested the importance of understanding mechanisms controlling transcription of the Ccna1 gene. The lack of cell lines derived from male germ cells made it necessary to analyze the Ccna1 promoter in these cells in vivo in transgenic mice (Lele and Wolgemuth 2004). Serial deletions in the Ccna1 upstream sequence allowed us to define two functional segments of the promoter.…”
Section: 4 Regulation Of Expression Of the A-type Cyclins In The Gmentioning
confidence: 99%
“…Analysis of transgenes carrying the genomic fragment of mouse Ccna1 spanning −1.3 kb to +0.8 kb (designated 1.3cyA1lacZ) of the putative transcriptional start site, using a combination of X-gal staining and in situ hybridization, revealed expression specifically in spermatocytes at stages IX to XII of the cycle of the seminiferous epithelium (Lele and Wolgemuth 2004). No expression was observed in spermatogonia or earlier meiotic stages, a pattern that is similar to the narrow window of expression during spermatogenesis seen for the endogenous mouse gene.…”
Section: 4 Regulation Of Expression Of the A-type Cyclins In The Gmentioning
confidence: 99%
“…Transcriptional regulatory factors such as E2F, Rb, CDF-1 and perhaps the SWI/SNF chromatin remodelling complex have all been implicated in the function of these elements (Schulze et al 1995;Liu et al 1998b;Philips et al 1999;Coisy et al 2004), but they remain poorly characterized. It is of interest that the CDE/CHR elements are also found in the promoter proximal region of both the human and mouse cyclin A1 gene (Lele & Wolgemuth 2004). …”
Section: A-type Cyclinsmentioning
confidence: 99%